Case Report: Multimodal immunotherapeutic regimen (envafolimab + chemotherapy + radiotherapy) for four synchronous primary malignant neoplasms: a case report of 33-month survival and implications for tumor immunology - Liu, Yadong; Zhang, Yayu; Zhang, Yu; Duan, Xuejuan; Gao, Zhanjie; Zhang, Xianbo; Zhao, Jing (Frontiers in Oncology, 2026)
Multiple Primary Malignant Neoplasms (MPMNs) are defined as the presence of two or more independent malignant tumors in the same patient, either simultaneously or sequentially, presenting substantial diagnostic and therapeutic challenges. In recent years, immunotherapy—an emerging therapeutic modality—has shown notable clinical efficacy across a range of malignancies. This article reports a case of a patient with four concurrent primary malignancies who attained long-term survival following treatment with envafolimab injection. Using this case as a foundation, we discuss recent advances in immunotherapy for MPMNs, covering its mechanisms of action, clinical efficacy, therapeutic strategies, and current challenges. The goal is to provide a theoretical basis for clinical practice and identify future research directions.